Trade Liberalization Strategies : What Could South Eastern Europe Learn From Cefta and Bfta? - Adam, Antonis (IMF Working Papers; Working Paper ;, 2003)
This paper explores the effectiveness of the Central European Free Trade Area (CEFTA) and the Baltic Free Trade Area (BFTA). Estimates from a gravity model and bilateral trade data support the view that both CEFTA and BFTA helped expand regional trade and limit the emergence of a "hub-and-spoke" relationship between the CEECs and the European Union (EU). These empirical conclusions carry some important policy implications for the "second wave" of prospective EU members among Southeastern European Countries (SEECs). The paper argues that the SEECs should reconsider their bilateral approach to trade liberalization and move towards a multilateral free-trade area as exemplified by both the CEFTA and BFTA.